The Covid-19 pandemic in Greece through the lens of methodological synergy: Combining corpus linguistics and critical discourse analysis approaches - Elafropoulos, Dimitris (The Greek Review of Social Research, 2024)
Computational approaches have been increasingly used in social sciences in recent years. The present study investigates to what extent a triangulated framework of corpus linguistics and critical discourse analysis can shed light on cutting-edge approaches and offer new insights into social research. Big data sets that may be examined computationally reveal patterns, trends and co-occurrences of elements (Teubert & Krishnamurthy, 2007, p. 6). This research is based on analysing a 720-text corpus of political and scientific discourse (March 2020 - May 2022) of representatives of three main institutions (government, main opposition party, and Greek public health organisation). Mediated political and scientific discourse has been the primary source of information regarding the Covid-19 pandemic crisis. The computational techniques focus on the representation of the pandemic and the relevant collocations and concordances in an attempt to navigate afterwards through qualitative analysis. Findings indicate that the government constructed a ‘‘rescue narrative’’ while the main opposition party advocated working-class priorities. Conceptual metaphors regarding the pandemic were pervasive both in political and scientific discourse. Comparative studies among different countries could be conducted in the future.